Inorganic nanomaterial-reinforced hydrogel membrane as an artificial periosteum. (August 2022) - Ullah, Ismat; Hussain, Zahid; Zhang, Yajie; Liu, Xingzhu; Ullah, Salim; Zhang, Ye; Zheng, Penghui; Gao, Tong; Liu, Yuanshan; Zhang, Zhuangzhuang; Cao, Yi; Wang, Zhili; et al.
Highlights: Surface modification of Sr/Fe:HAp nanomaterials with photo-cross-linkable gelatin methacrylate improved the dispersion and crosslinking efficacy of nanomaterials in the hydrogel. The co-cross-linking approach of nanocomposite hydrogel membrane enhanced the biomechanical properties. The fabricated GelMA-MSr/Fe:HAp nanocomposite hydrogel membrane as regenerative periosteum. This artificial periosteum exhibits superior angiogenesis and neo-bone formation in vivo . The co-cross-linking of gelatin and Sr/Fe:HAp provides a new potential for bone tissue engineering. Abstract: Repairing large bone defects remains challenging with the major risks of delayed union or even non-union. From the perspective of bone development and clinical experience, the periosteum is critical for protection, vascularization, neomineralization, and of note plays an indispensable role in bone reconstruction and regeneration. On the other hand, many artificial periosteums were designed solely for protection and lacked the functional capacity for osteogenesis and angiogenesis. In this work, we designed an inorganic nanomaterials-reinforced gelatin hydrogel membrane as an artificial periosteum using an organic and inorganic co-cross-linked approach for improving the durable angiogenesis and osteogenesis in bone repairing. Bioactive strontium (Sr) and/or iron (Fe) substituted hydroxyapatite (HAp) nanomaterials chemically surface-decorated with photo-cross-linkable gelatin methacrylate (GelMA) were subsequently blended into GelMA solution to develop an organic/inorganic co-cross-linked hydrogel membrane. These co-cross-linked hydrogel membranes/scaffolds confirmed the improved mechanical property, prolonged degradation life, stable pH value, better biomineralization, and steady ion release associated with evenly dispersed Sr and/or Fe substituted HAp nanomaterials into the GelMA hydrogel. In vitro experiments evaluation proved that when compared with the single cross-linked GelMA-Sr/Fe:HAp scaffold, the co-cross-linked GelMA-MSr/Fe:HAp membrane greatly enhanced osteogenic differentiation including alkaline phosphatase activity and production of matrix mineralization while retaining the stable pH value of the local environment, which was conducive to cell viability, proliferation, and adhesion. Furthermore, GelMA-MSr/Fe:HAp membrane is defined as a superior artificial periosteum with high capacity in osteogenesis and angiogenesis for promoting fresh and mature lamellar bone development in Sprague Dawley rat tibia defects. This organic/inorganic strengthening structure of co-cross-linked hydrogel membrane could be implied a promising approach for forming of advanced and new periosteum biomaterials with excellent handling and remarkable bone reconstruction properties. Graphical abstract: Image, graphical abstract